Religiositas di Tengah Bencana Gempa Bumi Lombok-Indonesia - Suprapto Suprapto; Miftahul Huda (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2020)
There are two different opinions about the relationship between religiosity and post-disaster trauma. First, it is religiosity that helps the mental recovery of disaster survivors. Second, religiosity does not have a significant role in the lives of disaster survivors. This research supports to verify both opinions, through field observations and interviews with earthquake survivors in Lombok-Indonesia. Herbert Blumer, researchers used symbolic interactions. The results found a positive relationship between religiosity and mental recovery. Although this disaster has caused massive casualties, misery and loss, it has released significant difficulties in religious awareness. The nuances of religiosity found at the Lombok disaster site are also not only about ritual worship, but also more inclusive social relations, and more authentic relationships with supernatural realms and natural environment.